Influencia del potencial financiero en las microempresas del sector comercial de Cajabamba para contribuir a su crecimiento económico año 2017 - López Martell, Lizbani Sulin (2018)
In order to achieve the objectives of the microenterprises, they develop their activities looking for their economic and financial growth, but often they can not alone, and therefore they go to third parties to obtain money and thus open more markets in other places, increase its commercialization, build or acquire new plants, or make another investment in which the company can benefit. As a problem, many microbusinesses in the Cajabamba district do not have a financial advisor to guide them and help them choose an investment or make an appropriate decision on which financing to choose, taking a bad decision and having as a consequence the high costs that You have to pay for the use of that required money, causing the economic slowdown, quantitative losses or even the closing of the business, being detrimental to the purpose for which this company was created. This could be avoided if the microentrepreneurs were financially advised and thus be able to finance themselves and invest appropriately and that, in this way, the microenterprise can have a financial potential that allows them to grow economically. The main objective of the present investigation is to demonstrate that the financial potential of the microenterprises of the Cajabamba district has a positive impact on their economic growth for the year 2017. For the present investigation, a sample was taken of 34 commercial microenterprises of the Cajabamba district, engaged in the trade of articles, footwear and agricultural inputs. The investigation was carried out using the descriptive method, for which, the existent relations between the variables were analyzed, making use of surveys, observations, interviews to entrepreneurs and bibliographical sources. The most important result obtained is that financing (one of the indicators of financial potential) does have a positive effect on the overall growth of the microenterprise, but that these do not give it due importance.